Escape from antibody-mediated immune suppression in vitro by delayed-type hypersensitivity reaction. - Muscoplat, C C (1977)
Anti-sheep erythrocyte antiserum suppressed the in vitro immune response of swine spleen cells to sheep erythrocytes. Inhibition of the in vitro anti-sheep erythrocyte response was also observed in neonatal spleen cells, which were obtained from piglets recently fed colostrum. Addition of purified protein derivative (PPD) to spleen cell cultures prepared from animals previously sensitized to Mycobacterium bovis reversed the immunosuppression caused by passive antibody. Passive antibody regulation was dose dependent; low doses of anti-sheep erythrocyte antiserum caused enhancement, whereas higher doses resulted in complete inhibition of anti-sheep erythrocyte responses. Addition of PPD to cultures of sensitized cells containing passive antibody resulted in progressively increased antibody responses as the dose of anti-sheep erythrocyte antibody increased. PPD addition also reversed maternal antibody suppression of in vitro 2-week-old neonatal spleen cell responses providing these animals were sensitized with M. bovis at the time of birth.